Social representations of corruption and violence and its relationship with social moral reflection in young urban and rural areas of different regions of Peru - Arenas Iparraguirre, Carlos (2011)
Research identified the social representations of corruption and violence and its relationship to levels of socio-moral reflection of young people in urban areas and rural country. We evaluated to  268 young people from urban and rural areas, of both sexes , aged between 18 and 25 years, developing focus groups to identify the social representations of corruption and violence and a questionnaire of socio-reflection  proposed moral Gibbs, Arnold and Morgan and adapted by Grimaldo (2002). No significant relationship was found between socio-moral reflection and social representation of corruption and violence. There is a moral development mostly  located in the  interpersonal harmony ,while a third of the population is located in an instrumental relativist orientation and moral development level reached by youth for the pre-conventional and conventional. The levels of socio-moral  reflection in Pucallpa be located in the Stage 2 (instrumental relativist orientation) while the other regions evaluated the Stage 3 ( interpersonal harmony orientation would be predominant. Corruption is a social practice of adaptation that allows orientation to interpersonal harmony , often have a pessimistic view about the possibility  of eliminating them. The social representation of violence would be  directly related to corruption, in the sense of giving greater value to the individual and immediate  benefit to social welfare or collective.